Social policy, architecture, and gender inclusivity: Enhancing women's experiences in public spaces on Ismet Pasha Street, Uşak, Turkey - Bugday, Gozde; Mokhtarshahi Sani, Rafooneh (Palgrave Macmillan Ltd, 2025)
Gender inclusivity in urban spaces remains a critical challenge in contemporary society, with women often experiencing limitations in their access to and comfort within these environments. Social policies play a crucial role in shaping urban spaces to be more inclusive and equitable, yet the intersection between policy, design, and women's everyday experiences in the urban realm requires further investigation. This study examines how architectural design in urban contexts interacts with social policies and women's lived experiences, focusing on Ismet Pasha Street in U & scedil;ak, Turkey, as a microcosm of small-city urban space dynamics. The research employs a qualitative approach that combines grounded theory and thematic analysis, integrating counter-mapping as a core method-conducted over two distinct seasons-together with semi-structured interviews involving women from diverse social and cultural backgrounds. The findings reveal that despite universal design principles, the street's current urban configuration fails to adequately address women's needs for comfort and privacy, largely due to male-dominated spaces and traditional sociocultural norms in urban spaces. While religious factors play a role, the study found that male-dominated society and family dynamics have a more significant impact on women's public space participation. The research identifies key areas for improvement, including the need for women-specific spaces, enhanced green areas, better shading elements, and child-friendly features. This study contributes to the broader discourse on spatial justice by highlighting how sociocultural factors must be considered alongside universal design principles to create truly inclusive urban public spaces for women.
Keywords: Urban space; Social policies; Women; Architectural design; Inclusivity; U & scedil;ak; Turkey